PERIODONTAL DISEASE AND DIABETES IN UZBEKISTAN’S PUBLIC HEALTH CONTEXT - Yusupova M.M. (Central Asian Journal of Medicine, 2025)
This paper examines the bidirectional link between diabetes and periodontal disease amid Uzbekistan’s growing burden of non-communicable diseases. Using national and international evidence, it applies a syndemic framework to reconceptualize these conditions as biologically and socially interconnected. While nutrition and infectious disease control have improved, oral complications of diabetes remain overlooked in national care strategies. The study advocates for screening, interdisciplinary training, and oral health integration into chronic disease policy.